The Promise of the Pandemic and the (Becoming) Totus Christus - Ryliškytė, Ligita (Theological studies, 2021)
The COVID-19 pandemic both causes a profound suffering and holds a promise of new growth. This article argues that the key condition for the possibility of growth is a discerning and creative transformation of evil into good through the diffusion of divine friendship, which takes place in accord with constantly shifting probabilities of the emergent world order. Decisively inaugurated in the Christ event, the redemptive shift in this order is concretely realized in history as the dialectical unification of all things in Christ, the cruciform becoming of the totus Christus.